NREGA, Asset Creation and Positive Discrimination: Evidence From Madhya Pradesh. - Kumar, Yogesh and Sah, D.C (2012)
It has been argued that caste hierarchies in India have been influenced by Social Sector Investment. Access to better education, health, income and in decision making in village democracy is, perhaps, a significant change that resulted in empowering the vulnerable section of rural society. More recently, the implementation of demand driven employment guarantee scheme has tried to positively influence access to employment and income of the deprived sections of the society. Added cash in the hands of households from marginalized section also means economic transformation.